ENHANCEMENT OF MATHEMATICS LEARNING USING RECIPROCAL TEACHING APPROACH FOR CLASS X STUDENTS OF VOCATIONAL SCHOOL OF MUHAMMADIYAH KRETEK - Istiqomah Istiqomah; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was conducted because the independence of learning mathematics in class X AK 1 even semester of SMK Muhammadiyah Kretek Bantul in the 2015/2016 academic year was still lacking. The purpose of this study is to improve the independence of learning mathematics using a reciprocal teaching approach to class X AK 1 even semester of SMK Muhammadiyah Kretek Bantul in the academic year 2015/2016. This research is a type of classroom action research. Subjects in this study were students of class X AK 1 even semester of SMK Muhammadiyah Kretek Bantul in the 2015/2016 academic year. While the object studied in this study is the reciprocal teaching approach as an effort to improve mathematics learning independence of students of class X AK 1 even semester of SMK Muhammadiyah Kretek Bantul in the academic year 2015/2016. The study was conducted in 2 cycles, namely, cycle I and cycle II, each cycle consisting of 2 meetings. Cycle I and cycle II use the Reciprocal Teaching Approach. Data collection techniques in this study, namely observation, interviews, tests, and documentation. Analysis of the data used is descriptive qualitative. The results showed that learning using the Reciprocal Teaching Approach could improve mathematics learning independence of students of class X AK 1 even semester of SMK Muhammadiyah Kretek Bantul in the academic year 2015/2016. This is evident from the results of observations of students 'mathematics learning independence in each cycle has increased, namely the average percentage of students' mathematics learning independence in cycle I amounted to 48.5119% who achieved enough criteria, and in the second cycle increased to 64.88095% which achieved good criteria. The results of interviews with students showed a positive response to the independence of students learning mathematics.